Microsatellite genotyping of Trypanosoma evansi isolates from livestock of different agro-ecological zones of India - SAINI, VIJESH KUMAR; SINGH, JARNAIL; KAUSHIK, JYOTI; SARKHEL, SOUTI PRASAD; KUMAR, SANJAY; YADAV, S C; GUPTA, A K; KUMAR, RAJENDER (The Indian Journal of Animal Sciences, 2014)
The present study deals with genetic diversity analysis by microsatellite genotyping of Trypanosoma evansi isolates collected from different livestock hosts (horse, donkey, camel and cattle) inhabiting different geographical location in North and North-western parts of India. Out of 12 microsatellite loci used in the study 10 successfully genotyped 6 T. evansi isolates, and 6 of them were found polymorphic. At 6 microsatellite loci (TB8/11, TB11/29, TB10/1, TB1/8, TB3/3 and TB4/2) observed number of alleles per locus ranged from 3 (TB8/11) to 6 (TB4/2) with a mean of 4.83±1.75 and effective number of alleles ranged from 2.11 (TB8/1) to 5.00 (TB4/2) with a mean value of 3.32±1.16. At 4 microsatellite loci (TB11/13, TB2/19, TB11/1 and TB8/1) observed (na=2) as well as effective (ne=2) number of alleles were the same. The observed heterozygosity varied from 0.16 (TB8/11) to 1.00 (TB11/13, TB2/19, TB10/1, TB1/8 and TB4/2) with a mean of 0.76±0.37. The expected value of heterozygosity (Levene’s) varied from 0.48 (TB8/1) to 0.88 (TB4/2) with a mean of 0.59±0.23. Polymorphism information content (PIC) value ranged from 0.34 (TB8/1) to 0.77 (TB4/2), indicating that TB11/29, TB10/1, TB1/8, TB3/3 and TB4/2 microsatellite loci were highly informative (PIC>0.5). Neighbour-joining tree analysis indicated different clustering of isolates based on allelic sharing. In the present study, 6 microsatellite markers were found useful to determine genetic diversity among Indian T. evansi isolates.